2020
DOI: 10.31602/jpaiuniska.v6i1.3368
|View full text |Cite
|
Sign up to set email alerts
|

Manajemen Pengelolaan Zakat Bagi Pengurus Masjid

Abstract: Ta’mir Masjid adalah organisasi kelembagaan Masjid yang terdiri dari beberapa orang dan mempunyai kewajiban memakmurkan Masjid. Pemahaman yang masih rendah dalam manajemen pengelolalan ZISWAF sehingga diperlukan penuluhan dan pendampingan bagi Pengurus Masjid dalam melakukan Pengelolaan Zsiwaf. Metode yang dilakukan dengan menggunakan dua pendekatan yaitu pelatihan dan pendampingan. Hasil pelatihan Pengurus mulai memahami manajemen pengelolaan ziswaf baik pengumpulan maupun pendistrusian dan pendayagunaan dana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Beberapa penelitian yang berhubungan dengan penelitian yang dilakukan peneliti antara lain: Penelitian yang ditulis oleh Huda et al (2020) yang berjudul "Manajemen Pengelolaan Zakat Bagi Pengurus Masjid". Hasil dari penelitian ini mengungkapkan bahwa proses pengumpulan dan pembagian zakat di Desa Prambatan dilakukan melalui Masjid Baiturrahman pada akhir bulan Ramadhan.…”
Section: Kajian Literaturunclassified
“…Beberapa penelitian yang berhubungan dengan penelitian yang dilakukan peneliti antara lain: Penelitian yang ditulis oleh Huda et al (2020) yang berjudul "Manajemen Pengelolaan Zakat Bagi Pengurus Masjid". Hasil dari penelitian ini mengungkapkan bahwa proses pengumpulan dan pembagian zakat di Desa Prambatan dilakukan melalui Masjid Baiturrahman pada akhir bulan Ramadhan.…”
Section: Kajian Literaturunclassified
“…Meanwhile, negative sentiment (26%) is an abstract sentiment derived from literature explaining the weakness of the ZISWAF from an Islamic social finance industry. Some literature discusses the management of ZISWAF that is not optimal (Huda et al, 2020;Janah et al, 2021;Ferald et al, 2022). Other research has also linked the conditions of the Covid-19 pandemic with ZISWAF which is expected to be a solution to existing social problems (Purwanto et al, 2021;Amirudin & Sabiq, 2021;Sari & Syariati, The problem of ZISWAF management that is not optimal is generally caused by the moral hazard that is carried out in managing funds.…”
Section: Meta-data Analysismentioning
confidence: 99%
“…Additional investigations have revealed that ZISWAF management is still not ideal, necessitating a variety of fixes. In their study of ZISWAF management for mosque administrators, Huda et al (2020) noted that there are a number of typical issues that can occur, including a lack of understanding of ZISWAF management and the use of outdated management models that increase the possibility of mistakes. The research employs a strategy that includes mentoring and training methods for ZISWAF managers.…”
Section: Moral Hazard As a Phenomenon In Ziswaf Institutions?mentioning
confidence: 99%
“…It shows that paying zakat is the principal worship as praying. Besides the relationship with Allah SWT (hablumminallah), zakat also has a relationship with society to cultivate a sense of compassion (hablumminannas) (Huda et al, 2012;Manurung, 2014;Triyani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%